Do Women in Nepal Like Playing a Mobile Game? MANTRA: A Mobile Gamified App for Improving Healthcare Seeking Behavior in Rural Nepal - Kayastha, Rachya; Mueller, Sonja; Yadav, Punam; Kelman, Ilan; Boscor, Andrei; Saville, Naomi; Arjyal, Abriti; Baral, Sushil; Fordham, Maureen; Hearn, Gareth; Kostkova, Patty (Frontiers in Public Health, 2021)
In Low and Middle Income Countries (LMIC), one of the causes of maternal and child mortality is a lack of medical knowledge and consequently the inability to seek timely healthcare. Mobile health (mHealth) technology is gradually becoming a universal intervention platform across the globe due to ubiquity of mobile phones and network coverage. MANTRA is a novel mHealth intervention developed to tackle maternal and child health issues through a serious mobile game app in rural Nepal, which demonstrated a statistically significant knowledge improvement in rural women. This paper explores the perceptions and usability of the MANTRA app amongst rural women and Female Community Health Volunteers (FCHVs) in Nepal. Despite the challenges of a target user group with limited educational levels and low smartphone experience, all participants viewed the MANTRA app with approval and enthusiasm. They were willing to engage further with the mHealth intervention and to share their experience and knowledge with fellow community members. Participants also showed an increase in awareness of danger signs enabling them to make better informed health decisions in the future. FCHVs viewed the app as a validation tool providing and support for greater impact of their efforts in rural Nepal. Growing mobile ownership, network coverage and availability of smartphones along with acceptance of the prototype MANTRA app in rural communities suggest encouraging prospects for mHealth interventions to be incorporated in the national health infrastructure in Nepal and other LMICs.